Mutations in the TOPORS gene cause 1% of autosomal dominant retinitis pigmentosa - Bowne, Sara J. (Molecular Vision, 2008)
PURPOSE: The purpose of this project was to determine if mutations, including large insertions or deletions, in the recently identified RP31 gene topoisomerase I-binding arginine-serine rich (RS) protein (TOPORS), cause an appreciable fraction of autosomal dominant retinitis pigmentosa (adRP). METHODS: An adRP cohort of 215 families was used to determine the frequency of TOPORS mutations. We looked for mutations in TOPORS by testing 89 probands from the cohort without mutations in other known adRP genes. Mutation detection was performed by fluorescent capillary sequencing and by multiplex ligation probe amplification. RESULTS: Two different TOPORS mutations, p.Glu808X and p.Arg857GlyfsX9, were each identified in one proband. Patients with these mutations exhibited clinical signs typical of advanced adRP. No large deletions or insertions of TOPORS were identified in our study. CONCLUSIONS: Point mutations and small insertions or deletions in TOPORS cause approximately 1% of adRP. Large deletions or insertions of TOPORS are not an appreciable cause of adRP. Contrary to previous reports, no distinct clinical phenotype was seen in these patients.